KAJIAN KRIMINOLOGIS ABORTUS PROVOCATUS YANG DILAKUKAN OLEH REMAJA DI KOTA AMBON - Yonna Beatrix Salamor (SASI, 2015)
provocatus abortion grown very rapidly in the community. Even more worrying some cases abortion occurring provocatus committed by juveniles, the same thing was happening in the city of Ambon. Women and teens are currently do not have a better option in addition to the actions that are inconsistent with the moral that an abortion